Sufentanil Reduces Emergence Delirium in Children Undergoing Transthoracic Device Closure of VSD After Sevoflurane-Based Cardiac Anesthesia - Xu,Ning (2020)
Abstract Objective: The aim of this study was to evaluate whether sufentanil can reduce emergence delirium in children undergoing transthoracic device closure of ventricular septal defect (VSD) after sevoflurane-based cardiac anesthesia. Methods: From February 2019 to May 2019, 68 children who underwent transthoracic device closure of VSD at our center were retrospectively analyzed. All patients were divided into two groups: 36 patients in group S, who were given sufentanil and sevoflurane-based cardiac anesthesia, and 32 patients in group F, who were given fentanyl and sevoflurane-based cardiac anesthesia. The following clinical data were recorded: age, sex, body weight, operation time, and bispectral index (BIS). After the children were sent to the intensive care unit (ICU), pediatric anesthesia emergence delirium (PAED) and face, legs, activity, cry, consolability (FLACC) scale scores were also assessed. The incidence of adverse reactions, such as nausea, vomiting, drowsiness and dizziness, was recorded. Results: There was no significant difference in age, sex, body weight, operation time or BIS value between the two groups. Extubation time (min), PEAD score and FLACC scale score in group S were significantly better than those in group F (P<0.05). No serious anesthesia or drug-related side effects occurred. Conclusions: Sufentanil can be safely used in sevoflurane-based fast-track cardiac anesthesia for transthoracic device closure of VSD in children. Compared to fentanyl, sufentanil is more effective in reducing postoperative emergence delirium, with lower analgesia scores and greater comfort.